Analisis Yuridis Konsolidasi Tanah - Rumagit, Joni; Idham, Idham (ARBITER: Jurnal Ilmiah Magister Hukum, 2021)
The legal basis for land consolidation in the context of improving the quality of the resedential environtment is based on the nationally regulated lawas and regulations, including Article 33 paragraph (3) of the 1945 Costitution of the Republic of Indonesia, Articles 2, 6, 12, 14 of the UUPA, law No. 1 of 2011 concerning Housing and Settlements, Law No. 32 of 2009 concering Environmental Protection and Management, Law No. 26 of 2007 concerning Spatial Planning and the Head of the National Land Agency issued Regulation of the Head of The National Land Agency Number 4 of 1991 concerning Land Consolidation. The supporting factors for land consolidations in order to improve the quality of residential environtment are the Collaboration between Land Office and several related agencies in the land consolidation. While the inhibiting factor for soil consolidation in order to improve the quality of the residential environtment is the lack of knowlage of land consolidation participants regarding land consolidations.